Formative Assessment: A Significant Facilitator of Student Learning - Yang, Yaodong (Science Insights Education Frontiers, 2024)
In recent decades, formative assessment has garnered substantial interest of teachers and educational researchers. Definitions of formative assessment vary in the literature. Relatively well-accepted among them is the one that describe it as the process of seeking and interpreting evidence for learners and their teachers to determine where the learners are in their learning, where they need to go and how best to get there (Antoniou & James, 2014). As opposed to summative assessment, formative evaluation gives comprehensive evaluation and feedback throughout the learning process of students, with the purpose of assisting students in identifying learning gaps, modifying learning methods, and enhancing learning outcomes. Common forms of formative assessment include quizzes, observation records, face-to-face conversations, questionnaires, feedback, student self-assessment, etc. It is meant to evaluate not only students’ academic performance but also their progress in learning attitudes, learning strategies, emotional skills, and other aspects (Wu, 2023).